CODE-MIXING AND CODE-SWITCHING MANIFESTATION IN COMPUTER MEDIATED COMMUNICATION (CMC) – AN ANALYSIS ON THE WRITTEN INTERACTION BETWEEN ENGLISH DEPARTMENT MEMBERS - Khalid, Ilyani Abd (Universitas Muhammadiyah Prof. DR. HAMKA, 2023)
Code-mixing (CM) and code-switching (CS) are common patterns that can be observed in the spoken and written language among multilingual speakers. The manifestation of code-mixing and code-switching in Computer Mediated Communication (CMC) is inevitable in the wake of the technological waves that pervaded everyday’s interactions. CMC is defined as any form of communication via the usage of two or more electronic devices, which includes the interaction using social media platforms and applications like WhatsApp and WeChat. This study observes the instances of the code-mixing and code-switching occurrences in the CMC between USAS’ English Language Department members. The data collected is analysed to determine the pattern and the factors influencing the mixing and switching to happen. The analysed CMC data is derived from the text message conversations of the Department’s WhatsApp group over the span of 16 days; of the heaviest traffic use. This study also examines the languages (and derivatives) used in the code-switching, and explore the factors contributing to the manifestation. Keywords: Computer-Mediated Communication, CMC, code-switching, code-mixing, bi/multilingualism